Massa por Argamassa A "Libraria de Babel" e o Sonho de Totalidade - Basile, Jonathan (punctum books, 2019)
"Mass by Mortar presents an in-depth exploration of one of the greatest illusionists in literature, Jorge Luis Borges. His tale" The Library of Babel "is an illustrious example of its playful ability, though not only because of the inverted world imagined in it in the past. which a library, which supposedly contains all possible combinations of all letters, words, and books, is searched by devout librarians for divinely prefabricated truths, for one also has to deal with the irony of Borges's narration, which constantly puts check the narrator's claims about the universality of the library, including the very possibility of exhausting the possible meanings through a combinatorial process.